Oculomotor Adaptation Elicited By Intra-Saccadic Visual Stimulation: Time-Course of Efficient Visual Target Perturbation - Panouillères, Muriel T. N.; Gaveau, Valerie; Debatisse, Jeremy; Jacquin, Patricia; LeBlond, Marie; Pélisson, Denis (Frontiers in Human Neuroscience, 2016)
Perception of our visual environment strongly depends on saccadic eye movements, which in turn are calibrated by saccadic adaptation mechanisms elicited by systematic movement errors. Current models of saccadic adaptation assume that visual error signals are acquired only after saccade completion, because the high speed of saccade execution disturbs visual processing (saccadic “suppression” and “mislocalization”). Complementing a previous study from our group, here we report that visual information presented during saccades can drive adaptation mechanisms and we further determine the critical time window of such error processing. In 15 healthy volunteers, shortening adaptation of reactive saccades toward a ±8° visual target was induced by flashing the target for 2 msec less eccentrically than its initial location either near saccade peak velocity (‘PV’ condition) or peak deceleration (‘PD’) or saccade termination (‘END’). Results showed that, as compared to the ‘CONTROL’ condition (target flashed at its initial location upon saccade termination), saccade amplitude decreased all throughout the ‘PD’ and ‘END’ conditions, reaching significant levels in the second adaptation and post- adaptation blocks. The results of 9 other subjects tested in a saccade lengthening adaptation paradigm with the target flashing near peak deceleration (‘PD’ and ‘CONTROL’ conditions) revealed no significant change of gain, confirming that saccade shortening adaptation is easier to elicit. Also, together with this last result, the stable gain observed in the ‘CONTROL’ conditions of both experiments suggests that mislocalization of the target flash is not responsible for the saccade shortening adaptation demonstrated in the first group. Altogether, these findings reveal that the visual “suppression” and “mislocalization” phenomena related to saccade execution do not prevent brief visual information delivered ‘in-flight’ from being processed to elicit oculomotor adaptation.